Cognitive dimensions of creativity: What makes the difference between creative and non creative university students? - Morais, Maria de Fátima (2009)
This paper analyses the contribution of specific cognitive functions on creative performance. The main question was which cognitive variables differentiate extreme levels of creative performance and therefore can characterize highly creative college students. A sample of Portuguese university students of Fine Arts and Literature (n=166) took part in this study. A battery of verbal and figural cognitive tasks, as well as two kinds of creative tasks (text and poster production) have been considered. Results showed that there were mostly the same cognitive dimensions (figurative reasoning, divergent thinking, insight problem solving, and problem-finding), which differentiate extreme levels of creative performance in both text and poster productions. These results are discussed considering the relevance of the cognitive approach to explain creativity. Some practical ideas, possible to put into the educational context, are also discussed.